2004
DOI: 10.1038/sj.bjc.6602010
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan plus gemcitabine vs irinotecan for the second-line treatment of patients with advanced non-small-cell lung cancer pretreated with docetaxel and cisplatin: a multicentre, randomised, phase II study

Abstract: To compare irinotecan (CPT-11) þ gemcitabine vs CPT-11 alone as second-line treatment for patients with advanced non-small cell lung cancer (NSCLC) progressing after docetaxel -cisplatinum-based therapy. A total of 147 evaluable, pretreated patients, with NSCLC, received either gemcitabine (1000 mg m À2 , days 1 and 8) þ CPT-11 (300 mg m À2, day 8) (Group A, n ¼ 76) or CPT-11 (300 mg m À2 , day 1) (Group B, n ¼ 71), every 3 weeks. All patients were evaluable for response and toxicity. The objective response ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Similarly, a 31% response rate was observed (Nakanishi et al, 1999) with a weekly administration of irinotecan and cisplatin in 16 patients with refractory NSCLC. A recent multicenter, randomised phase II study, which compared the irinotecan/gemcitabine combination vs irinotecan in NSCLC patients pretreated with taxanes plus cisplatinum, demonstrated a poor antitumour activity of irinotecan (ORR ¼ 4.2%) (Georgoulias et al, 2004) as already reported by Negoro et al (see Ferrigno and Buccheri, 2000). Taken together, the improved antitumour activity of irinotecan/cisplatin combination (Nakanishi et al, 1999;Kakolyris et al, 2001) and the poor activity of single agent irinotecan or cisplatin in the second-line setting seem to indicate an in vivo synergism between the two agents as it has been shown in preclinical studies (Kano et al, 1992;Kudoh et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a 31% response rate was observed (Nakanishi et al, 1999) with a weekly administration of irinotecan and cisplatin in 16 patients with refractory NSCLC. A recent multicenter, randomised phase II study, which compared the irinotecan/gemcitabine combination vs irinotecan in NSCLC patients pretreated with taxanes plus cisplatinum, demonstrated a poor antitumour activity of irinotecan (ORR ¼ 4.2%) (Georgoulias et al, 2004) as already reported by Negoro et al (see Ferrigno and Buccheri, 2000). Taken together, the improved antitumour activity of irinotecan/cisplatin combination (Nakanishi et al, 1999;Kakolyris et al, 2001) and the poor activity of single agent irinotecan or cisplatin in the second-line setting seem to indicate an in vivo synergism between the two agents as it has been shown in preclinical studies (Kano et al, 1992;Kudoh et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…TOP1 (topoisomerase 1) plays a crucial role in DNA replication and maintaining genome stability by regulating the supercoiling state of DNA. TOP1 is also the cellular target for irinotecan, an agent approved for advanced or metastatic NSCLC 36. Higher expression of TOP1 in KRAS mutant patients and correlation to survival suggests that TOP1 inhibitors might have increased benefit when administered to treat patients with a KRAS mutant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized phase II trials have compared combination chemotherapy with monotherapy in the secondline setting. Georgoulias et al 22 compared irinotecan plus gemcitabine with irinotecan alone as a second-line treatment for patients with progression of advanced NSCLC after cisplatin plus docetaxel-based therapy. No signifi cant differences were observed between the groups in time to tumor progression (7.5 months vs 5.0 months) or overall survival (9.0 months vs 7.0 months).…”
Section: Discussionmentioning
confidence: 99%